Dynamical management of dejitter buffers based on speech quality - do Valle, Raquel F; de Carvalho, Leandro S G; Aguiar, Regeane B; Mota, Edjair S; Freitas, Diógenes (The IEEE symposium on Computers and Communications, 2010)
Owing to packet forwarding throughout different paths and asynchronous behavior of TCP/IP networks, voice packets of a voice flow may arrive at their destination with varying delay. This impairment, known as jitter, is smoothed at the receiver side by applying dejitter buffer algorithms, which store some packets for an amount of time before playout. This paper presents a manager algorithm of dejitter buffers, which monitors network loss, delay and jitter conditions and change the dejitter buffer algorithm used by the receiver's softphone according to the parameters conjuncture in order to improve speech quality.